PEMBERDAYAAN UMKM PADA MASA NEW NORMAL UNTUK MENOPANG EKONOMI MASYARAKAT - Yayuk Yuliana; Wan Dian Safina (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
Micro, small and medium enterprises (MSMEs) are businesses that are run by individuals, households, or small business entities. One of the obstacles to the advancement of MSMEs is not only in product quality, but how a micro, small and medium enterprise (MSME) is able to do good marketing. The period of the Covid-19 pandemic has provided a change in perspective on the perspective of product marketing and promotion. Activities that used to be carried out face-to-face, as long as it is recommended to stay at home, cannot be carried out anymore. Likewise with marketing and promotional activities carried out through exhibitions and bazaars. This has a big impact on the resilience of the "fake" cake culinary business in Suka Maju Village, Medan Johor Village. Through this assistance, the group becomes more able to have other media options for marketing and product promotion, without having to meet face to face. The results of this activity have been the implementation of the management function in the activity plan, improving marketing skills and good management so that there is an increase in turnover in micro, small and medium enterprises (MSMEs).